Bat Employs a Conserved MDA5 Gene to Trigger Antiviral Innate Immune Responses - Wang, Jie; Lin, Zhenyu; Liu, Qiuju; Fu, Feiyu; Wang, Zhaofei; Ma, Jingjiao; Wang, Hengan; Yan, Yaxian; Cheng, Yuqiang; Sun, Jianhe (Frontiers in Immunology, 2022)
Bats are important hosts for various zoonotic viral diseases. However, they rarely show signs of disease infection with such viruses. As the first line for virus control, the innate immune system of bats attracted our full attention. In this study, the Tadarida brasiliensis MDA5 gene (batMDA5), a major sensor for anti-RNA viral infection, was first cloned, and its biological functions in antiviral innate immunity were identified. Bioinformatics analysis shows that the amino acid sequence of batMDA5 is poorly conserved among species, and it is evolutionarily closer to humans. The mRNA of BatMDA5 was significantly upregulated in Newcastle disease virus, avian influenza virus, and vesicular stomatitis virus-infected bat TB 1 Lu cells. Overexpression of batMDA5 could activate IFNβ and inhibit vesicular stomatitis virus (VSV-GFP) replication in TB I Lu cells, while knockdown of batMDA5 yielded the opposite result. In addition, we found that the CARD domain was essential for MDA5 to activate IFNβ by constructing MDA5 domain mutant plasmids. These results indicated that bat employs a conserved MDA5 gene to trigger anti-RNA virus innate immune response. This study helps understand the biological role of MDA5 in innate immunity during evolution.